Rationality of creating a new national meat product «Meat bread» - Abimuldina, S.T.; Koftanyuk, N.V.; Mardanova, Z.Zh.; Zhussupbayeva, D.A.; Valishina, G.L.; Smetanska, I. (Fundamental and Experimental Biology, 2018)
The article considers scientifically-based selection of raw materials for obtaining a meat product with a health-promoting effect for ecologically unfavorable regions. A resource-saving production technology has been developed and the formulation of the meat product has been modeled for the prevention of diseases associated with a deficit of macronutrient and micronutrient elements, containing native animal origin proteins and a vitamins complex positively having a positive impact on the human body. Solving the problem of reduction of morbidity caused by adverse environmental situation is possible in two directions: improvement of the environment and the creation of new functional food products, making possible the correction of nutritional status, correcting adverse effect of environment. The article presents the results of the determination of functional and technological properties, amino acid composition, microbiological indices, peroxide number, and the term of product storage is determined. Such physicochemical parameters as protein, moisture, fat and sodium chloride were determined as part of the study. The microbiological analysis consisted of determining the Coliform bacteria and the number of mesophilic aerobic and facultative aerobic microorganism.